Azacytidine for acute myeloid leukemia in elderly or frail patients: a phase II trial (SAKK 30/07). Issue 1 (January 2014) - Passweg, Jakob R.; Pabst, Thomas; Blum, Sabine; Bargetzi, Mario; Li, Qiyu; Heim, Dominik; Stussi, Georg; Gregor, Michael; Leoncini, Leda; Meyer-Monard, Sandrine; Brauchli, Peter; Chalandon, Yves; et al.
Abstract This phase II trial treated elderly or frail patients with acute myeloid leukemia (AML) with single-agent subcutaneous azacytidine at 100 mg/m2, on 5 of 28 days for up to six cycles. Treatment was stopped for lack of response, or continued to progression in responders. The primary endpoint was response within 6 months. A response rate ≥ 34% was considered a positive trial outcome. From September 2008 to April 2010, 45 patients from 10 centers (median age 74 [55–86] years) were accrued. Patients received four (1–21) cycles. Best response was complete response/complete response with incomplete recovery of neutrophils and/or platelets (CR/CRi) in eight (18%; 95% confidence interval [CI]: 8–32%.), 0 (0%) partial response (PR), seven (16%) hematologic improvement, 17 (38%) stable disease. Three non-responding patients stopped treatment after six cycles, 31 patients stopped early and 11 patients continued treatment for 8–21 cycles. Adverse events (grade ≥ III) were infections (n = 13), febrile neutropenia (n = 8), thrombocytopenia (n = 7), dyspnea (p = 6), bleeding (n = 5) and anemia (n = 4). Median overall survival was 6 months. Peripheral blood blast counts, grouped at 30%, had a borderline significant association with response (p = 0.07). This modified azacytidine schedule is feasible for elderly or frail patients with AML in an outpatient setting with moderate, mainly hematologic, toxicity and response in a proportion of patients, although the primary objective was not reached.